Art and modernism in socialist China: unexplored international encounters 1949-1979 - Kong, Shuyu; Andrews, Julia F.; Zheng, Shengtian (Routledge Research in Art History, 2024)
"This edited volume will be the first book examining the art history of China's socialist period from the perspective of modernism, modernity, and global interactions. The majority of chapters are based on newly available archival materials and fresh critical frameworks/concepts. By shifting the frame of interpretation from socialist realism to socialist modernity, this study reveals the plurality of the historical process of developing modernity in China, the autonomy of artistic agency, and the complexity of an art world conditioned, yet not completely confined, by its surrounding political and ideological apparatus. The unexpected global exchanges examined by many of the authors in this study and the divergent approaches, topics, and genres they present add new sources and insights to this research field, revealing an art history that is heterogeneous, pluralistic and multi-layered. The book will be of interest to scholars working in art history, art and politics, and Chinese studies"--